Temperature- and stress-dependent scaling of ferroelectric hysteresis in soft and hard PZT bulk ceramics - R. Yimnirun (2018)
Lead zirconate titanate (Pb(Zr1-xTix)O3 or PZT) ceramics have been employed extensively in sensors and actuators, as well as smart systems. The dynamic hysteresis characteristics have become important consideration in these applications. Therefore, we performed experiments on soft and hard PZT bulk ceramics to investigate the effects of electric field-frequency, electric field-amplitude, mechanical stress, and temperature on the hysteresis area especially the scaling form. The hysteresis profiles under the effects of relevant parameters were obtained. At stress-free condition, the investigation found the area scales with frequency and amplitude in power-law form; however, with different set of exponents in comparing to those in the investigation on thin films structure. This indicates the dimensional dependence of the exponents. On the other hand, with compressive stresses turning on, the same set of the exponents with the stress-free condition is found to confirm universality. Similar situation was also found with experiments done at various temperatures. The study is therefore successful in modelling how the hysteresis area changes with stress and temperature at high-frequencies which provides another step closer in understanding real bulk ferroelectric materials. Copyright © 2007 MS&T'07®.